The role of attitute towards SME food advertisements on intention to purchase Malaysian SME food product - Olanrewaju, Hazeez Abdulsalami (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
This research aims to identify the factors that influence small and medium-sized enterprises (SME) food consumers' intention to purchase the products by underpinning the Theory of Planned Behaviour (TPB) and Theory of Attitude towards advertisements. The SME food industry plays a very important role in the Malaysian economy, especially to increase the GDP and to create job opportunities for the masses. In order to identify the factors that affect SME food consumers in Malaysia, data was collected from 357 consumers from the Klang Valley area in Malaysia. The conceptual framework is based on the Theory of Planned Behaviour and Theory of Attitude towards SME food advertisements and the relationships among a number of variables which include attitude, subjective norms, perceived behavioural control and attitude towards SME food advertisement. These variables were tested using the Structural Equation Modelling (SEM). The empirical finding of the research shows that three out of the four hypotheses were supported. It is found that attitude toward SME food product, subjective norms and perceived behavioural control have a significant positive effect on SME food consumers' intention to purchase while attitude toward SME food advertisements is found to be insignificant. These results confirm the success of the proposed theoretical framework in achieving the objectives of this study. The findings of the research will be useful for practitioners and marketing managers in the SME food industry. Researchers and academicians can also benefit from the research findings of this study as it has helped the understanding of the of SME food industry in Malaysian.